1979
DOI: 10.1246/bcsj.52.2136
|View full text |Cite
|
Sign up to set email alerts
|

The Thermal Decompositions of Dialkyl Peroxides

Abstract: With the purpose of obtaining information needed for hazard prevention, pure liquid dialkyl peroxides (di-t-butyl peroxide (1), bis(1-methyl-1-phenylethyl) peroxide (2), t-butyl 1-methyl-1-phenylethyl peroxide (3), 2,5-bis(t-butyldioxy)-2,5-dimethylhexane (4)) were subjected to thermal-decomposition experiments, in which thermal analyses were conducted by the use of a thermogravimetry (TG)-differential scanning calorimetry (DSC) apparatus equipped with a pinholed pan with a minute pinhole. From the DSC curves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…As all samples except MEKPO were prepared as 70 wt% with liquid paraffin, the thermal decomposition behaviour became mild and less violent than that of original and it was found that dilution had a strong influence on the thermal decomposition of POs (Uetake, 1979).…”
Section: Thermal Decomposition Behaviour Of Posmentioning
confidence: 99%
“…As all samples except MEKPO were prepared as 70 wt% with liquid paraffin, the thermal decomposition behaviour became mild and less violent than that of original and it was found that dilution had a strong influence on the thermal decomposition of POs (Uetake, 1979).…”
Section: Thermal Decomposition Behaviour Of Posmentioning
confidence: 99%